Evaluation of the i-STAT Blood Gas Analysis System in Cardiovascular Surgery - Çiğdem Unal Kantekin; Müjgan Ercan; Esra Firat Oğuz; Ertan Demirdaş; Kıvanç Atılgan; Mesut Sipahi; Ferit Çiçekçioğlu (Medical Laboratory Technology Journal, 2018)
The aim of this study was toinvestigate the compatibility of the parameters measured with the i-STAT blood gas analyser and the conventional blood gas analyser Rapid Point 500 (Siemens Healthcare Diagnostics, USA) in patients who underwent cardiovascular surgery. This clinical study included fifty patients undergoing coronary artery bypass surgery. Fifty whole blood samples were portioned and measured on the i-STAT and RP500 laboratory analyzers. The compatibility between pH, pCO2, pO2, Hb, Na+, K+, iCa2+ and glucose values was investigated.There was a good correlation of the i-STAT analyser with the RP500 analyser, with the exception Hb and Na+. Also all parameters except for Hb and ionized calcium were found to be within acceptable range in terms of clinical decision limits. It is very important that the point-of-care devices give accurate results as well as quick results. For this reason, we absolutely think that the point of care devices should be subjected to external and internal quality control programs, users should be trained regularly and feedback studies should be done.